Analisis Stilistika (Sajak) pada Surah Al-‘Asr dan Implikasinya terhadap Pembaca - Rohmatulloh, Acep Ihsan (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2024)
This research aims to discuss the stylistics of the Al-Qur'an, as well as provide an in-depth analysis of the poetry in Surah Al-'Asr and the effects it has on readers and listeners. Stylistics is very important for linguistic studies and literary studies. Stylistics can contribute to research on language style, which is the main element for achieving various forms of meaning in literary works, because literary works cannot be separated from the use of language style and beauty. The research method used in this research is the analytical descriptive method. After the required data is collected, the data will be elaborated with descriptive explanations. Sound harmony is realized in the form of consonant and vowel sounds. Overall, several verses in Surah al-'Asr end in rhyme with the vowel /i/. while the vowel sounds contained in several of the words of the poem are the vowel /a/ with a total of 3 letters, the vowel /u/ with a total of 1 letter, and the vowel /i/ with a total of 4. The harmony of these sounds can also be felt by listeners when al- When the Qur'an is listened to, the harmonious and beautiful sounds of course give rise to psychological aspects for the listeners who read the verses. Furthermore, the harmony of sound also has an effect on the meaning produced. So that harmonious sounds produce beautiful and harmonious meanings